Tradition und Moderne in der Literatur der Schweiz im 20. Jahrhundert - Pormeister, Eve (Humaniora: Germanistica, 2008)
The papers in this volume show the presence of Gottfried Keller, the literary father figure of Swiss literature, in the texts of the Swiss authors from 1960ies, such as Otto F. Walter, Hugo Loetscher, Adolf Muschg, and Urs Widmer. Although these authors work in the democratic tradition of Switzerland and have an almost identificatory relationship to Keller, their role in the changed political life of the 20th century is completely different from that of their great literary model. The volume also contains studies on other Swiss literary classics, such as Robert Walser and Meinrad Inglin, as well as later authors, such as Max Frisch and Friedrich Dürrenmatt, Erica Pedretti, Thomas Hürlimann, Silvio Blatter, Peter Stamm, and Gertrud Leutenegger.